Longitudinal Outcomes of Left Ventricular Outflow Tract Obstruction in Aortic Stenosis Versus Hypertrophic Obstructive Cardiomyopathy - Joy Yi-Shan Ong; Tony Yi-Wei Li; Aloysius Sheng-Ting Leow; Swee-Chye Quek; William Kok-Fai Kong; Weiqin Lin; Ping Chai; Tiong-Cheng Yeo; Raymond Ching-Chiew Wong; Ching-Hui Sia; Kian-Keong Poh (Medicina, 2025)
Background and Objectives: Aortic stenosis (AS) and hypertrophic obstructive cardiomyopathy (HOCM) are two disease entities that result in left ventricular outflow tract (LVOT) obstruction. We sought to evaluate the longitudinal outcomes of fixed obstruction in severe valvular AS versus dynamic flow obstruction in HOCM. Materials and Methods: Consecutive data with index echocardiographic diagnoses of severe AS and HOCM were collected in a tertiary academic centre between 2010 and 2017. Demographics, comorbidities and clinical outcomes were compared. Results: A total of 134 patients were studied. In the AS group, the mean MPG was 57.2 mmHg ± 13.9, the mean AVA was 0.7 cm2 ± 0.2, and the mean Vmax was 4.7 m/s ± 0.5 (p < 0.001). In the HOCM group, the mean LVOT gradient was 60.1 mmHg ± 35.5, the mean IVSd was 17.5 mm ± 4.6, and the mean LVPWd was 12.9 mm ± 2.9 (p < 0.001). Kaplan–Meier curves showed lower cumulative survival with an early separation in heart failure outcomes in the AS arm compared with the HOCM arm (p = 0.023). Similarly, there were higher rates of all-cause mortality for AS compared with HOCM (p = 0.001). For the multivariable Cox regression analysis, AS was significantly associated with a higher incidence of heart failure compared with HOCM after adjusting for the baseline demographics, comorbidities and echocardiographic parameters. There were no significant differences in terms of stroke or cardiovascular (CV) hospitalisation outcomes between the two cohorts. Conclusions: Fixed LVOT obstruction in AS was associated with worse outcomes of heart failure and all-cause mortality compared with dynamic LVOT obstruction in HOCM. Severe AS was an independent predictor of heart failure outcomes after adjustments.